Kajian Pertumbuhan dan Hasil Cabai Rawit terhadap Berbagai Dosis Pupuk Hayati dan Konsentrasi Indol Acetic Acid (IAA) - Simanjuntak, Ls Hari Candra; Harsono, P.; Hasanudin, Hasanudin (Akta Agrosia, 2017)
Cultivation of cayenne pepper is still much dependent on the use of inorganic fertilizers on a large scale with a high dose. Optimizing the use of inorganic fertilizers needs to be done so that the cost of chili farming can be minimized and more environmentally friendly. Optimization of cayenne pepper cultivation can be done through intensification efforts that is through the addition of biological fertilizers and IAA growth regulators. It is necessary to study the use of biological fertilizer and IAA on the growth and yield of cayenne pepper. The objective of this research is to get the optimum dosage of biofertilizer and IAA concentration for growth and yield of cayenne pepper. This research was conducted from September to January 2016. This study used Completely Randomized Design (RAL) with two factors. The first factor was biological fertilizer consisting of: B0 (without biological fertilizer), B1 (2 g per polybag), B2 (4 g per polybag), B3 (6 g per polybag) and second factor ie IAA spray concentration: without IAA), I1 (2 mgL -1), I2 (4 mgL-1), I3 (6 mgL-1) were repeated four times to obtain 64 experimental units. The results showed that biological fertilizer treatment significantly affect the leaves leaf variation with the optimum dosage of biomass fertilizer that is 2.29 g per plant produces leaf area 5.59 cm2. Furthermore very significant effect on fruit weight variables with increased dosage of 2 g can increase the weight of chili pepper fruit. While the interaction of dosage of biological fertilizer and IAA concentration did not significantly affect each observation variables.